2020
DOI: 10.21037/atm-20-5115
|View full text |Cite
|
Sign up to set email alerts
|

Ulinastatin alleviates cerebral ischemia-reperfusion injury in rats by activating the Nrf-2/HO-1 signaling pathway

Abstract: Background: Ulinastatin, a urinary trypsin inhibitor, is one of the widely used auxiliary drugs in the rescue of acute circulatory failure. This study aims to explore the protective mechanisms of ulinastatin on cerebral ischemia-reperfusion (I/R) injury.Methods: A cerebral MCAO was established with middle cerebral artery occlusion (MCAO) in Sprague Dawley (SD) rats. Western blotting was employed to show protein expression. Oxidative stress markers [reactive oxygen species (ROS), superoxide dismutase (SOD), mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Moreover, the expression level of several stroke-associated inflammatory genes, such as VCAM-1, SMAHD-1, and DDAH1, were significantly upregulated in COVID-19 positive patients, indicating that the inflammatory response may play potential roles in mediating COVID-19-associated stroke. As mentioned above, the expression levels of HMOX1, LTC4S, and ACTB seem to have negative correlation relationships with the risk of cerebral ischemia ( Freiberg et al, 2010 ; Nitti et al, 2018 ; Cui et al, 2020 ; Yang et al, 2020 ), the significant downregulation of HMOX1, LTC4S, and ACTB in PBMC samples from COVID-19 positive patients may indicate possible molecular mechanisms between COVID-19 and stroke. However, further clinical and functional studies using COVID-19 patient samples or animal models are highly needed to investigate direct viral infection effects and indirect inflammatory effects on human brains by SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Moreover, the expression level of several stroke-associated inflammatory genes, such as VCAM-1, SMAHD-1, and DDAH1, were significantly upregulated in COVID-19 positive patients, indicating that the inflammatory response may play potential roles in mediating COVID-19-associated stroke. As mentioned above, the expression levels of HMOX1, LTC4S, and ACTB seem to have negative correlation relationships with the risk of cerebral ischemia ( Freiberg et al, 2010 ; Nitti et al, 2018 ; Cui et al, 2020 ; Yang et al, 2020 ), the significant downregulation of HMOX1, LTC4S, and ACTB in PBMC samples from COVID-19 positive patients may indicate possible molecular mechanisms between COVID-19 and stroke. However, further clinical and functional studies using COVID-19 patient samples or animal models are highly needed to investigate direct viral infection effects and indirect inflammatory effects on human brains by SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 78%
“…Numerous studies have reported the effectiveness of HMOX1, a stress-responsive protein induced by various oxidative agents, in cardiology by aspects such as inflammation, antioxidant function, apoptosis, hypoxia, and ischemia/reperfusion injury ( Wan et al, 2020 ). The upregulation of HMOX1 during cerebral ischemia revealed a protective effect on neuronal cell against oxidative stress ( Nitti et al, 2018 ; Cui et al, 2020 ). A previous study also showed that the dysfunction or downregulation of LTC4S, one of the key enzymes of the 5-lipoxygenase pathway, was associated with increased risk of venous thromboembolism and ischemic stroke ( Freiberg et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Nrf2‐sMaf heterodimer then binds to AREs to activate hundreds of genes in the nucleus that regulate energy metabolism, anti‐inflammatory signal transduction and exogenous detoxification enzymes. Among these genes, the expression of many antioxidant enzymes, such as HO‐1, NQO1, SOD, glucuronyltransferase and glutathione s‐transferase, is the most closely related to oxidative damage 47–49 . Downstream antioxidant genes activated by Nrf2 transcription, particularly HO‐1, are an extremely important response to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological histological damage of the whole brain in mice was evaluated by using Hematoxylin and eosin (HE) staining as previously described. 23 Briefly, after 24 h of reperfusion, the brain tissues were fixed with 4% paraformaldehyde, dehydrated by alcohol and embedded in paraffin. The brains were cut into 5-μm-thick sections and incubated with HE reagents, followed by photographed under a light microscopy in five randomly selected fields.…”
Section: Methodsmentioning
confidence: 99%